2020
DOI: 10.3390/ijerph17217788
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Recognition Patterns Demonstrated by Construction Workers

Abstract: Construction workers fail to recognize a large number of safety hazards. These unrecognized safety hazards can lead to unintended hazard exposure and tragic safety incidents. Unfortunately, traditional hazard recognition interventions (e.g., job hazard analyses and safety training) have been unable to tackle the industry-wide problem of poor hazard recognition levels. In fact, emerging evidence has demonstrated that traditional hazard recognition interventions have been designed without a proper understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Likewise, estimates from Australia suggest that up to 57% of safety hazards can possibly remain unrecognized [22]. Similar patterns of poor hazard recognition have been highlighted in construction workplaces across nations and geographical regions [16,18,22,23,43].…”
Section: Construction Hazard Recognitionmentioning
confidence: 68%
See 1 more Smart Citation
“…Likewise, estimates from Australia suggest that up to 57% of safety hazards can possibly remain unrecognized [22]. Similar patterns of poor hazard recognition have been highlighted in construction workplaces across nations and geographical regions [16,18,22,23,43].…”
Section: Construction Hazard Recognitionmentioning
confidence: 68%
“…Unfortunately, evidence suggests that poor hazard recognition levels are a widespread and persistent problem in construction workplaces [15,16]. In fact, evidence suggests that over 40% of safety hazards may remain unrecognized in typical construction workplaces [17,[20][21][22][23]. Moreover, past research has demonstrated that all construction industry stakeholders-whether workers, engineers, managers, or superintendents-lack effective hazard recognition skills [16,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…It is proven that safety performance in the construction sector can be improved by providing effective safety training [ 16 , 66 ]. Due to the dynamic nature of construction work environments, it is important to provide regular training [ 67 , 68 ] so that employees are aware of the changing environments and associated risks. This is important because increased safety awareness, knowledge and skills lead to the successful and effective implementation of the safety program [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggest that workers and organisations value information and feedback from inspectors (Niskanen et al, 2014;Umeokafor et al, 2022). Furthermore, studies have shown that workers fail to recognise many hazards (Uddin et al, 2020), while a lack of knowledge is a barrier to implementing effective safety management (Buniya et al, 2021). Studies on such OHS campaigns are rather limited and often relate to very specific topics.…”
Section: Impact Of Deterrents On Accidents At Workmentioning
confidence: 99%